Application of First-principle Process Control Model in Optimization of a Polymerization Technology - Balaskó, Balázs; Németh, Sándor; Abonyi, János (Acta Agraria Kaposváriensis, 2006)
Nowadays the optimization of chemical processes is a basic expectation. Chemical industry is one of the most automated industries; therefore it has the potential for continuous improvements by analyzing the enormous quantity of process data with some a priori knowledge and by utilizing the results of previously unknown associations and information about the investigated technology. Beyond data based black- and grey-box modeling techniques, the traditional model-based approach is also needed to analyze and improve the engineering knowledge implemented in the distributed process control system (DCS) as equations and algorithms. This paper deals with the advanced process control system of an operating polymerization technology. Modeling the control system and applying the experience of plant operators, sensibility-analysis between process values and product quality, state-estimating and parameter identification tools, control system and technology qualifying tools or new product operating points could be achieved. The purpose of this paper is to review the possibilities of supervising a complex, hierarchical control system and present its applicability on an real industrial example.